Industrialización acuícola; salchicha doña Tilapia. - Ortiz Narváez, Verónica Elizabeth (2017)
The constant need of man to satisfy the great demands of food for the population and the continuous evolution of new products in the market, makes necessary the search for new alimentary alternatives and the use of innovative raw materials for the development of products that are nutritional contribution in the diet of the human being. The work presented below aims at the industrialization of raw materials such as blue tilapia from the Pastaza province, sector Veracruz that is the place dedicated to this arduous work of the cultivation and commercialization of the fish; Due to this exploitation, an alternative was considered and the need to transform this matter into processed product, so the research consists of combining three types of meats such as blue tilapia (Oreochromis aurus), pig and fat, at different concentrations resulting in Better treatment of T5 (a3b1) (40% of tilapia meat, 20% of pork and 30% of iron) with the addition of potato starch in 5% as indicated in the current norm; And 5% in additives and condiments to obtain a product that is appetizing to the consumer. A homogeneous emulsion characteristic for the production of "Doña Tilapia" sausage was obtained obtaining a final product of quality within the parameters established by the legislation for this type of food guaranteeing its nutritional value with the following results: Fat (9g-14%); Cholesterol (17mg-6g); Sodium (290mg-12%); Carbohydrates (2g-1%) and Protein (5g-10%), in the same way the freshness and innocuity of the product, for which the laboratory analyzes of the nutritional content and microbial load (Escherichia coli; Salmonella) were carried out. Are within the established parameters and the product does not present any danger to the consumer. Its retail price is $ 4.80 per pound of product.